Seychelles : Request for an Arrangement Under the Extended Fund Facility. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Seychelles' Request for an Arrangement Under the Extended Fund Facility (EFF). In the five years following the 2008 balance of payments and debt crisis, the authorities have successfully enacted a comprehensive program of reforms. Despite the success of the program, important risks and challenges remain. To face these challenges, the authorities have requested a successor EFF arrangement with the IMF. This program will help support their macroeconomic policies and protect reserve coverage over the extended period, while they carry out wide-ranging structural reforms necessary to support improvement in macroeconomic conditions, lock-in stabilization, and reduce the country's vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet